KOMODIFIKASI “HALAL” PADA KAMPANYE VAKSIN DI INDONESIA - M. Tazri; Arina Himatul Husna (Universitas Muhammadiyah Jember, 2022)
This study discusses messages in government communications about vaccination campaigns. The object of research is the government's message in the vaccination campaign with the